An N-terminal double-arginine motif maintains type II membrane proteins in the endoplasmic reticulum. - Schutze, M P (1994)
Use of alternative initiator methionines in human invariant (Ii) chain mRNA results in the synthesis of two polypeptides, Iip33 and Iip31. After synthesis both isoforms are inserted into the endoplasmic reticulum (ER) as type II membrane proteins. Subsequently, Iip31 is transported out of the ER, guiding MHC class II to the endocytic pathway, whereas Iip33, which differs by only a 16 residue extension at the N-terminus, becomes an ER resident. Mutagenesis of this extension showed that multiple arginines close to the N-terminus were responsible for ER targeting. The minimal requirements of this targeting motif were found to be two arginines (RR) located at positions 2 and 3, 3 and 4 or 4 and 5 or split by a residue at positions 2 and 4 or 3 and 5. Transplanting an RR motif onto transferrin receptor demonstrated that this motif can target other type II membrane proteins to the ER. The characteristics of this RR motif are similar to the KK ER targeting motif for type I membrane proteins. Indeed, RR-tagged transferrin receptor partially localized to the intermediate compartment, suggesting that like the KK motif, the RR motif directs the retrieval of membrane proteins to the ER via a retrograde transport pathway.